Efforts to Increase Corporate Value Based on Environmental Performance and Corporate Governance with Corporate Financial Performance as Intervening Variables in LQ 45 Companies - Nursaid Nursaid; Amalina Maryam Zakiyyah; Mochamad Rochmadoni; Nailatul Ilmi Nafi'ah; Nurul Qomariah (Budapest International Research and Critics University, 2023)
The corporate value paradigm is conventionally measured by the company's ability to generate maximum profits and prosperity for the owners of the company. This research was conducted on companies included in the LQ 45 Index. The purpose of this study was to determine the impact of environmental performance and corporate governance on financial performance and firm value in companies with an LQ 45 Index. The research population was companies with an LQ 45 Index totaling 45 companies with an analysis period of 2020 to 2022. The data analysis method used is smart PLS analysis. The results showed that environmental performance had a positive and significant effect on financial performance, corporate governance had a significant effect on financial performance, environmental performance had a positive and significant effect on firm value, corporate governance had a positive but not significant effect on firm value, financial performance had a positive effect and significant to value